2010
DOI: 10.2478/v10013-010-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of dosimetric variation due to interfraction organ movement in High Dose Rate Interstital (MUPIT) brachytherapy for gynecologic malignancies

Abstract: Ten patients with cancer of uterine cervix who underwent interstitial brachytherapy using MUPIT templates were CT scanned (CT1) using which bladder, rectum and CTV were delineated.The treatment plan PCT1 was generated and optimized geometrically on the volume. CT scan (CT2) was repeated before the second fraction of the treatment CTV and critical organs were delineated.The plan (PCT2) was created by reproducing the Plan PCT1 in the CT2 images and compared with PCT1. Bladder, Rectum and CTV percentage volume va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Velumurugan et al observed that the CTV mean dose varies from +9.8% to −13.3%. Out of 10 patients the mean dose was more than the prescribed dose in seven patients and less in three patients [10]. The maximum variation to CTV dose was estimated to be around 13%.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Velumurugan et al observed that the CTV mean dose varies from +9.8% to −13.3%. Out of 10 patients the mean dose was more than the prescribed dose in seven patients and less in three patients [10]. The maximum variation to CTV dose was estimated to be around 13%.…”
Section: Discussionmentioning
confidence: 88%
“…Velumurugan et al evaluated MUPIT implantation in patients with carcinoma cervix. In their study they recommended to repeat CT and re-plan before each fraction [10]. In our study imaging and planning was done before the first fraction.…”
Section: Discussionmentioning
confidence: 98%
“…Velmurugan et al 11 studied the dosimetric variation due to inter-fraction organ movement in HDR interstitial (MUPIT) brachytherapy for gynaecological malignancies in ten patients. They estimated the variation in the volume of the clinical target.…”
Section: Discussionmentioning
confidence: 99%
“…Velmurugan et al [18] suggested that the variation is significant and CT imaging for each fraction should be done to minimize the error in gynecological patients. CT/MRI imaging before each fraction can be an effective way to find the tumor shrinkage, edema and applicator displacement.…”
Section: Discussionmentioning
confidence: 99%